2013
DOI: 10.1371/journal.pone.0061968
|View full text |Cite|
|
Sign up to set email alerts
|

A Prospective Study on the Incidence of Postoperative Venous Thromboembolism in Korean Gastric Cancer Patients: An Inquiry into the Application of Western Guidelines to Asian Cancer Patients

Abstract: Several Western guidelines recommend the routine use of pharmacologic thromboprophylaxis for cancer surgery patients to prevent venous thromboembolism (VTE). However, the necessity of routine pharmacologic perioperative thromboprophylaxis in Asian gastric cancer (GC) patients has not been clearly determined. To determine the necessity of routine perioperative pharmacologic thromboprophylaxis in Korean gastric cancer patients, the incidence of postoperative VTE was prospectively evaluated in gastric cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Although perioperative pharmacologic thromboprophylaxis in cancer patients has not been routine practice in Korea, the present study demonstrated considerably low rates of postoperative VTE, which was consistent with previous retrospective studies reporting a VTE incidence of approximately 0.2% with stomach or colorectal cancer [31][32][33]. Moreover, Kim et al [34] recently reported a prospective study investigating the postoperative incidence of VTE in Korean patients with gastric cancer using routine Doppler ultrasonography between 5 and 12 days following surgery. In this study, postoperative VTE was detected in 9 (2.4%) of 375 patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although perioperative pharmacologic thromboprophylaxis in cancer patients has not been routine practice in Korea, the present study demonstrated considerably low rates of postoperative VTE, which was consistent with previous retrospective studies reporting a VTE incidence of approximately 0.2% with stomach or colorectal cancer [31][32][33]. Moreover, Kim et al [34] recently reported a prospective study investigating the postoperative incidence of VTE in Korean patients with gastric cancer using routine Doppler ultrasonography between 5 and 12 days following surgery. In this study, postoperative VTE was detected in 9 (2.4%) of 375 patients.…”
Section: Discussionsupporting
confidence: 90%
“…Although the postoperative VTE rate was low in Korean cancer patients, previous studies have highlighted that disease stage was a predictor of VTE development [31,32,[35][36][37]. In the prospective study conducted by Kim et al [34], stage IV disease was an independent risk factor for developing postoperative VTE with an 8.18-fold increased risk when compared to stage I disease. Therefore, despite the apparent protection against VTE conferred by the Asian ethnicity, patients with advanced stage cancers might have an increased risk of VTE during the postoperative period.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such low rates were found despite the fact that vast majority (82%) of patients were classified as high risk (based on Caprini Risk Score) and the majority did not receive VTE pharmacoprophylaxis (Table The majority of VTE occurred in patients who had undergone surgery for malignancy (83% versus 17% for benign disease). This is consistent with literature, where both the presence of a malignancy (especially in advanced stage) was associated with the development of postoperative VTE [11].…”
Section: Discussionsupporting
confidence: 93%
“…There were reports from India and other Asian countries regarding low incidence of DVT in malignancy following surgery. 7,21,22 Limitations of the Study Limitations of our study were small sample size and short follow up period, even though our results correlate with the reported incidence in Indian population. Further studies are needed including larger cohort and longer follow up.…”
Section: Discussionmentioning
confidence: 52%